Female sex as an independent risk factor for stroke in atrial fibrillation: Possible mechanisms - Cove, Christina L.; Albert, Christine M.; Andreotti, Felicita; Badimon, Lina; Van Gelder, Isabelle C.; Hylek, Elaine M. (Thrombosis and Haemostasis, 2014)
Atrial fibrillation (AF) is an independent risk factor for thromboembolism and stroke. Women with AF are at a higher overall risk for thromboembolic stroke when compared to men with AF. Recent evidence suggests that female sex, after adjusting for stroke risk profile and sex differences in utilisation of anticoagulation, is an independent stroke risk factor in AF. The inclusion of female sex has improved the accuracy of the CHADS2 stroke risk stratification schema (Congestive heart failure, Hypertension, Age 75 years or greater, Diabetes mellitus, and prior Stroke or TIA). The newly revised and validated schema, CHA2DS2-VASc, dichotomises age and incorporates female sex and vascular disease history. The pathophysiological mechanisms to explain this increased risk in women are not well understood. According to Virchow’s triad, thrombosis that leads to stroke in AF should arise from three co-existing phenomena: structural abnormalities, blood stasis, and a hypercoagulable state. Herein, we explore the sex differences in the biological processes that lead to thrombus formation as applied to Virchow’s Triad. The objective of this review is to describe the potential mechanisms behind the increased risk of stroke in AF associated with female sex.
Keywords: Atrial fibrillation; stroke; sex differences; anticoagulation